Estudo computacional do líquido GVL (Gama-valerolactona): Influência da quiralidade nas propriedades termodinâmicas - Colombari, Felippe Mariano (2017)
Besides its properties as a “green solvent”, organic molecule Gamma-valerolactone is also a chiral compound, presenting potential applications in enantioselective processes. Once obtained the adequate parameters for liquid phase simulations, different computational models were employed in order to investigate how chirality influences its thermodynamic properties. Under thermodynamic equilibrium, neither energetic nor structural differences between GVL racemic mixture and its enantiomeric pure counterparts were observed. Analysis of the most stable dimers extracted from a Monte Carlo simulation of the racemic mixture revealed subtle interaction energy differences when homochiral (RR and SS) pairs were compared to heterochiral (RS and SR) pairs, which indicated a subtle energetic preference for the homochiral ones. On the other hand, significant chiral discrimination were obtained using nonequilibrium methods. Solvation process for both R and S enantiomers of 1-chloro-1-aminoethane (CAE) in liquid SGVL via Thermodynamic Perturbation Theory resulted in a chemical potential nearly 3;3 kJ mol-1 lower for R-CAE when compared to S-CAE, indicating that the utilization of GVL as a chiral liquid could increase the yield of processes involving chiral species in condensed phase. Binding process of GVL molecules giving rise to both homochiral (SS) and heterochiral (SR) dimers in vacuum, via Umbrella Sampling method, could show that although both pairs had similar binding free energy values, major differences could be observed on these free energy profiles when higher molecular contact was imposed by Umbrella Sampling spatial confinement. Such binding process of GVL molecules was also studied in both RGVL and SGVL liquids. Thus, although lower binding free energy values were obtained, a nearly 20 % difference could be observed due to solvent chirality.